The impact of a compulsory web-based course on preservice teachers' motivational profile - THIERRY KARSENTI (Metaichmio Publications, 2007)
The goal of this research was to better understand the impact of the implementation of a compulsory Web-based course on preservice teacher motivation. Subjects were enrolled in a four-year teacher education program (n=429) in the province of Quebec (Canada). Our initial hypothesis was that the Web-based distance education course - designed to promote self-determination, affiliation, and a sense of competence - would positively impact the motivation of preservice teachers. Results presented are based on quantitative and qualitative data analysis. They demonstrate that a technologically rich learning environment can enhance motivation after only a few weeks.